The Power of Social Media in Driving Political Change: A Case Study on Bangladesh’s Regime Change in 2024 - Md. Amran Hossain; Md Mahady Hasan; Neel Wasantha (International Journal of Sociology and Law, 2025)
Social media is one of the most powerful tools brought into new opportunities not only for the marketing sector but also in the political sector for establishing networks within society, sharing information, and making awareness within the communities. SMN provides an exclusive platform for independent discussion for everybody. The former Prime Minister Sheikh Hasina was the head of the state and ruling the country under her power. The country was run consecutively for 3 terms, nearly 16 years without holding a free and fair election. This empirical case study is conducted to examine the power of social media in driving political change in Bangladesh. Secondly, how does the social media networking (SMN) platform impact changing the Gen Z mindset? Thirdly, how the social media tools has been used by the celebrity to mobilize the mass protest to remove the autocrat government in Bangladesh. On the other hand, to evaluate the opposition party like BNP gets benefit from the social media to get enough public strength to remove the autocratic government in Bangladesh. The survey was conducted to collect data through the questionnaire and 495 samples collected from all across Bangladesh. Meanwhile, non-random sampling techniques were also applied to get sample units in this research. The data was analyzed by using the SPSS software to get actual output. The collected all data was summarized to find out the frequency, percentage, correlation between the variables, and mean score of the research. The participant of respondents indicates the social media platform has influence on mass mobilization to change the regime in Bangladesh. The finding of the result shows that Facebook, Messenger, WhatsApp and TikTok are the favorite platforms used during the student movement. The significant of the result shows that social media was playing a vital key role in mobilizing all parties together and shaping the public opinion in one path to remove the Prime Minister of Sheikh Hasina on August 5th 2024.